Semarak Keluarga UMP cycles and cleans campus - Nor Salwana, Mohammad Idris (2022)
PEKAN, 26 September 2022 – More than 200 staff from Universiti Malaysia Pahang (UMP) participated in a 6.5 km cycling programme starting from the Multipurpose Hall, circling the campus while collecting garbage and cleaning the area around the university in the UMP 2022 Leisure Cycling Programme organised by the Registry Department in collaboration with the UMP Centre for Sports and Culture.